CHEMERIN AS A POTENTIAL REGULATOR OF MITOCHONDRIAL QUALITY CONTROL IN OBESE PATIENTS - M. A. Vulf; D. A. Shunkina (Skuratovskaia); V. Hung; A. A. Komar; P. A. Zatolokin; E. V. Kirienkova; N. D. Gazatova; L. S. Litvinova (Медицинская иммунология, 2021)
In obese patients, the relationship between the content of chemerin in blood plasma and the expression of genes TFAM, Drp1, MFN2, SOD, BAX, responsible for quality control of mitochondria, in insulin-dependent tissues (adipose tissue, liver) was revealed. The tissue-specific features of gene expression (TFAM, Drp1, MFN2, SOD, BAX), the number of mtDNA copies in the studied depots in obese patients were established. It has been proven that a change (decrease) in the number of mtDNA copies in insulin-dependent tissues can have a protective effect on mitochondria under conditions of increased oxidative stress. It was found that in patients without type 2 diabetes, an increase in chemerin production promotes the activation of the antioxidant system in the visceral adipose tissue but not in the liver. On the contrary, all obese patients with type 2 diabetes showed a decrease (compared with patients without type 2 diabetes) in the plasma level of chemerin. Thus, the low content of chemerin in the blood plasma in patients with type 2 diabetes mediates the formation of mitochondrial dysfunction in insulin-dependent tissues (adipose tissue, liver).